Towards a Multimodal Methodology for the Analysis of Translated/Localised Games - Bárbara Resende Coelho; Igor Antônio Lourenço da Silva (Domínios de Lingu@gem, 2016)
Multimedia materials require research methodologies that are able to comprehend all of their assets. Videogames are the epitome of multimedia, joining image, sound, video, animation, graphics and text with the interactivity factor. A methodology to conduct research into translation and localisation of videogames should be able to analyse all of its assets and features. This paper sets out to develop a research methodology for games and their translations/localisations that goes beyond the collection and analysis of “screenshots” and includes as many of their assets as possible. Using the fully localised version of the game Watchdogs, this papers shows how tools and technologies allow for transcending the mere analysis of linguistic contents within multimedia materials. Using software ELAN Language Archive to analyse Portuguese-language dubbed and English-language subtitled excerpts from the videogame, it was possible to identify patterns in both linguistic and audio-visual elements, as well as to correlate them.